The multi-domain exercise intervention for memory and brain function in late middle-aged and older adults at risk for Alzheimer's disease: A protocol for Western–Eastern Brain Fitness Integration Training trial - Chang, Yu-Kai; Erickson, Kirk I.; Aghjayan, Sarah L.; Chen, Feng-Tzu; Li, Ruei-Hong; Shih, Jia-Ru; Chang, Shao-Hsi; Huang, Chih-Mao; Chu, Chien-Heng (Frontiers in Aging Neuroscience, 2022)
Background Aging is associated with cognitive decline, increased risk for dementia, and deterioration of brain function. Modifiable lifestyle factors (e.g., exercise, meditation, and social interaction) have been proposed to benefit memory and brain function. However, previous studies have focused on a single exercise modality or a single lifestyle factor. Consequently, the effect of a more comprehensive exercise program that combines multiple exercise modalities and lifestyle factors, as well as examines potential mediators and moderators, on cognitive function and brain health in late middle-aged and older adults remains understudied. This study's primary aim is to examine the effect of a multi-domain exercise intervention on memory and brain function in cognitively healthy late middle-aged and older adults. In addition, we will examine whether apolipoprotein E (ApoE) genotypes, physical fitness (i.e., cardiovascular fitness, body composition, muscular fitness, flexibility, balance, and power), and brain-derived neurotrophic factor (BDNF) moderate and mediate the exercise intervention effects on memory and brain function. Methods The Western-Eastern Brain Fitness Integration Training (WE-BFit) is a single-blinded, double-arm, 6-month randomized controlled trial. One hundred cognitively healthy adults, aged 45–70 years, with different risks for Alzheimer's disease (i.e., ApoE genotype) will be recruited and randomized into either a multi-domain exercise group or an online educational course control group. The exercise intervention consists of one 90-min on-site and several online sessions up to 60 min per week for 6 months. Working memory, episodic memory, physical fitness, and BDNF will be assessed before and after the 6-month intervention. The effects of the WE-BFit on memory and brain function will be described and analyzed. We will further examine how ApoE genotype and changes in physical fitness and BDNF affect the effects of the intervention. Discussion WE-BFit is designed to improve memory and brain function using a multi-domain exercise intervention. The results will provide insight into the implementation of an exercise intervention with multiple domains to preserve memory and brain function in adults with genetic risk levels for Alzheimer's disease. Clinical trial registration ClinicalTrials.gov, identifier: NCT05068271.